Problematizar situações de ensino e desenvolver habilidades cognitivas: estudo sobre a importância das folhas para a planta e o ambiente - Küll, Cláudia Roberta (2018)
This research had its origin as the result concerning teaching methodologies by the researcher and teacher of Science for elementary school class, acting for 15 years in a private school in the countryside of the State of São Paulo. It aims to analyze the relations between problem-questions elaborated by the teacher with the cognitive skills developed by students of a 7th grade elementary class about the activities performed according to the elaborated arguments. Based on these purposes, the specific goals are: promoting a study about the importance of leaves to the plants that has an interdisciplinary, contextual and inquiry approach; analyzing the hypotheses elaborated by the students, relating them to the results obtained and promoting the reflection about scientific activities to develop high order cognitive skills. Therefore, the research questions were: which cognitive skills can be developed by 7th grade elementary school class departing from the study of the importance of leaves to the plant and the environment in an inquiry perspective? Which relations can be established between problem-questions proposed by the teacher according to the teaching purpose and the answers presented by the students to favour the argumentation and promote the development of high order cognitive skills? For this purpose, the research involves the participation of eighteen students of a 7th grade elementary class of a private school in the countryside of the State of São Paulo. We used as data acquisition instruments the written and photographic records from the students and the audio and video recording of the activities. The data analysis methodology was based in two instruments: to analyze the problem-questions proposed by the teacher we used the instrument created by Suart (2008) that categorizes them in three levels of requirement; whereas to analyze the arguments in the answers of the students towards understanding the cognitive skill levels we were inspired by the Suart and Marcondes (2009) instruments. Among the results of the problem-questions we could identify a bigger number of P2 questions; the P3 categorized questions were presented exclusively during the three final moments. According to the expected to the answers, we verify a movement in agreement with the problem-questions, in other words, in the initial activities there was a bigger number of answers categorized as N1 and N2, and according to the outgoing of the activities, the trajectory of the questions was followed, with the appearance and posterior concentration of N3 and N4 level answers. We detected that the student feels more motivated when he actively participates of the activities. We also noticed a direct relation between the student's performance in activities proposed and the level of requirement of the teacher in her problematizations. One of the contributions of this study stays in the development of an instrument that complements that one that already exists to analyze the students answers when referring to argumentation connected to cognitive abilities. A possible implication of this research to Science education area relies in considering the teaching-learning process done by using high order cognitive skills is desired, but the teaching strategies and the evaluation methods chosen by the teacher must be aligned to this end.